Gestión de activos de infraestructura en conjuntos residenciales (2022)
Residential sets are one of the most valuable assets, providing people with shelter, facilities for work, education, among others, so it is necessary to make a great effort to ensure that these buildings are maintained effectively and have optimal performance to improve their useful life, as well as to comply with regulations, health and safety standards, this will ensure greater reliability, safety, function, comfort and convenience for users (Martínez-Barrios, 2016).